Завдання та місце внутрішнього контролю в системі управлінського обліку суб’єктів господарювання - Саванчук, Тетяна Миколаївна; Savanchuk, Tetіana; Боровенська, Альона; Borovenska, Alona; Гервольська, Ірина; Hervolska, Irina (Видавничий дім «Гельветика», 2024)
У статті розглянуті погляди різних науковців на визначення різновидів та завдань внутрішнього контролю суб’єктів господарювання. Авторами встановлено, що на підприємствах в залежності від поставлених за¬вдань може застосовуватися внутрішньогосподарський, управлінський та фінансовий контроль. Обґрунтова¬но, що для раціональної організації управлінського обліку важливо використовувати результати всіх цих видів внутрішнього контролю, якщо вони здійснюються на підприємстві. Визначено основні завдання та місце вну¬трішнього контролю в системі управлінського обліку. Стаття містить практичні рекомендації, які можуть бути корисними суб’єктам господарювання в процесі інтеграції внутрішнього контролю та управлінського обліку в єдиній системі управління підприємством. Вона підкреслює важливість підтримання функціональних зв’язків між підрозділами управлінського обліку та внутрішнього контролю. The purpose of the article is to define the main tasks performed by internal control in the management accounting system and to justify the need to build functional connections between the units dealing with internal control and management accounting of economic entities. The specified direction of economic activity is relevant for any business entity, as it will allow to form in the management accounting system reliable, accurate and truthful information necessary for making management decisions. The research was conducted using the monographic method. The article examines the views of various scientists on the definition of types and tasks of internal control of economic entities. The authors established that economic entities, depending on the assigned tasks, can apply intra-economic, managerial and financial control. It is substantiated that for the rational organization of management accounting, it is important to use the results of all these types of internal control, if they are carried out at the enterprise. The main tasks of internal control in the management accounting system are determined. Such tasks include the following: ensuring the reliability of data about the actual state of the object, helping to identify weak points, ensuring protection against errors and abuses, tracking in the management system the procedures and principles that have been violated, identifying risk areas, opportunities and tools for elimination shortcomings, assessment of the validity and completeness of the target indicators of activity, analysis of financial indicators of activity and the validity of their application, ensuring the quality and timeliness of the submission of internal reports for making management decisions, evaluation of work centers of responsibility. The article contains practical tips and recommendations that may be useful to business entities in the process of integrating internal control and management accounting in a single enterprise management system. It emphasizes the importance of using the results of internal control in the management accounting system for effective management decision-making.
Task and place of internal control in the management accounting system of business entities
Keywords: управлінський облік; management accounting; внутрішній контроль; internal control; завдання; tasks; організація; organization; функціональні зв’язки; functional relationships